Hubungan Facial Injury Severity Scale dengan lama rawat inap pasien trauma maksilofasial di RSUP Prof. Dr R. D. Kandou Manado - Rampisela, Richard; Lumintang, Nico; Ngantung, Jan T. (Jurnal Biomedik : JBM, 2017)
Abstract: Maxillofacial trauma includes soft tissue injuries, such as burns, bruises and contusions, as well as fractures of facial bones that form the maxillofacial structure. The causes of maxillofacial fractures are traffic accidents, falls, hits, gun shots, sport accidents, and industrial accidents. Scoring system has been introduced as a tool to determine the prognostic value of patients with trauma. Facial trauma requires a different scoring system due to many dysfunctions that can occur afterwards. This study was aimed to determine the length of stay (LOS) of inpatients by using Facial injury Severity Scale (FISS). This was a correlation analytical study with a cross sectional design performed on inpatients of emergency care installation and medical records at Prof. Dr. R. D. Kandou Hospital from January 2015 through April 2016. The results showed that there were 52 patients in this study. Most of them were males (49 cases; 94.2%), aged 17-25 years (16 cases; 30.8%), refused to be operated (40 cases; 76.9%), patients with FISS 1-3 (42 cases; 80.7%), minor trauma (FISS <3), and zygoma fracture cases. The Pearson correlation coefficient test showed an r value = 0.646 (P <0.001) which stated that there was a significant relationship between FISS and LOS. Conclusion: Most patients with maxillofacial trauma had a FISS value less than 3 (mild trauma). Moreover, this FISS value could be used to estimate the length of stay.Keywords: maxillofacial trauma, facial fractures, FISSAbstract: Trauma maksilofasial mencakup cedera jaringan lunak seperti luka bakar, mencakup cedera jaringan lunak seperti luka bakar, memar, fraktur tulang fasial yang membentuk sturktur maksilofasial. Penyebab fraktur maksiofasial ialah antara lain kecelakaan lalu lintas, jatuh, pukulan, tembakan, kecelakaan olah raga, dan kecelakaan kerja. Sistem skoring digunakan untuk menentukan nilai prognostik pasien dengan trauma. Trauma fasial memerlukan sistem skoring yang berbeda karena banyak disfungsi yang dapat terjadi. Penelitian ini bertujuan untuk menentukan lama rawat inap dari pasien cedera fasial dengan menggunakan Facial injury Severity Scale (FISS). Jenis penelitian ialah korelasi analitik dengan desain potong lintang terhadap pasien rawat ianap dengan trauma maksilofasial di Instalasi Gawat Darurat dan Bagian Rekam Medik RSUP Prof. Dr. R. D. Kandou periode Januari 2015 s/d April 2016. Hasil penelitian mendapatkan 52 pasien dengan trauma maksilofasial. Sebagian besar pasien ialah laki-laki (49 kasus; 94,2%), berusia 17-25 tahun (16 kasus; 30,8%), menolak dioperasi (40 kasus; 76,9%), nilai FISS 1-3 (42 kasus; 80,7%), trauma ringan (FISS <3), dan fraktur tulang zygoma. Uji korelasi Pearson mendapatkan nilai r = 0,646 (P < 0,001) yang menunjukkan terdapatnya hubungan bermakna antara FISS dan lama rawat inap. Simpulan: Umumnya pasien dengan trauma maksilofasial mempunyai nilai FISS 3 (trauma ringan). FISS mempunyai nilai prognostik terhadap lama rawat inap.Kata kunci: trauma maksilofasial, fraktur fasial, FISS